Coupling dairy wastewaters for nutritional balancing and water recycling: sustainable heterologous 2-phenylethanol production by engineered cyanobacteria - Usai, Giulia; Cordara, Alessandro; Mazzocchi, Elena; Re, Angela; Fino, Debora; Pirri, Candido Fabrizio; Menin, Barbara (Frontiers in Bioengineering and Biotechnology, 2024)
Microalgae biotechnology is hampered by the high production costs and the massive usage of water during large-volume cultivations. These drawbacks can be softened by the production of high-value compounds and adopting metabolic engineering strategies to improve their performances and productivity. Today, the most sustainable approach is the exploitation of industrial wastewaters for microalgae cultivations, which couples valuable biomass production with water resource recovery. Among the food processing sectors, the dairy industry generates the largest volume of wastewaters through the manufacturing process. These effluents are typically rich in dissolved organic matter and nutrients, which make it a challenging and expensive waste stream for companies to manage. Nevertheless, these rich wastewaters represent an appealing resource for microalgal biotechnology. In this study, we propose a sustainable approach for high-value compound production on dairy wastewaters through cyanobacteria. This strategy is based on a metabolically engineered strain of the model cyanobacterium Synechococcus elongatus PCC 7942 (already published elsewhere) for 2-phenylethanol (2-PE). 2-PE is a high-value aromatic compound, employed as a fragrance in the food and cosmetics industry, thanks to its pleasant floral scent. Firstly, we assessed qualitatively the impact of four dairy effluents on cyanobacterial growth to identify the most promising substrates. Both tank washing waters and the liquid effluent of exhausted sludge resulted as suitable nutrient sources. Thus, we created an ideal buffer system by combining the two wastewaters, while simultaneously providing balanced nutrition and completely avoiding the need for fresh water. The combination of 75% liquid effluent of exhausted sludge and 25% tank washing waters, with a fine-tuning ammonium supplementation, yielded 180 mg L-1 of 2-PE and a biomass concentration of 0.6 gDW L-1 within ten days. While the mixture of 90% exhausted sludge and 10% washing waters allowed to the highest 2-PE (205 mg L-1) and biomass accumulation (0.7 gDW L-1), although in sixteen days. Through these treatments, the phosphates were completely consumed, and nitrogen was removed in a range of 74-77%. Overall, our approach significantly valorized the water recycling and the exploitation of valuable wastewaters to circularly produce marketable compounds via microalgae biotechnology, laying promising groundwork for subsequent implementation and scale-up.